2019
DOI: 10.1016/j.socec.2019.101459
|View full text |Cite
|
Sign up to set email alerts
|

Can whistleblower programs reduce tax evasion? Experimental evidence

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…Dyck et al (2010) concluded that the probability of fraud detection in healthcare became three times as high compared with other industries in which large False Claims Act bounty payouts were not offered to whistleblowers. It has also worked well with tax enforcement in the United States (Ventry 2014;Wilde 2017;Johannesen and Stolper 2017;Amir et al 2018;Masclet et al 2019). This fifth qui tam strategy exploits the reality that many insiders are likely to know about complex organisational crimes, while few or no outsiders do.…”
Section: Summarising Mixed Relational Prevention Through Softer Targetsmentioning
confidence: 98%
“…Dyck et al (2010) concluded that the probability of fraud detection in healthcare became three times as high compared with other industries in which large False Claims Act bounty payouts were not offered to whistleblowers. It has also worked well with tax enforcement in the United States (Ventry 2014;Wilde 2017;Johannesen and Stolper 2017;Amir et al 2018;Masclet et al 2019). This fifth qui tam strategy exploits the reality that many insiders are likely to know about complex organisational crimes, while few or no outsiders do.…”
Section: Summarising Mixed Relational Prevention Through Softer Targetsmentioning
confidence: 98%
“…Like Buckenmaier et al (2018) a year earlier, Masclet et al (2019) conducted an experiment to determine the efficacy of whistle blowing as a strategy for tackling tax evasion. Using 432 subjects from Canada and France, the study conducted an experiment whereby participants had the opportunity to report other participants who attempted to evade taxes in the tax game utilized in the experiment.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Their findings confirm that whistleblowing-based audit scheme decreases the monetary amount of evasion, improves the targeting of evaders and raises the tax levy. In their experimental study, Masclet et al (2019) investigate the effect of whistleblowing programs on tax evasion providing information to participants on the use of the tax revenues in three dynamic treatments: (i) a baseline treatment where tax evaders are obliged to pay taxes on the undeclared income and a penalty if audited, (ii) an information treatment in which participants are also informed about the income declaration rates of all other group members and (iii) a denunciation treatment in which each participant has the possibility to blow the whistle on others. They find that monitoring alone does not increase the declared income while allowing for blowing the whistle decreases tax evasion; moreover, informing participants that the tax revenue was used to finance an environmental public good has no significant impact on either tax compliance or peer reporting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a similar vein, in our experiment the tax revenues plus the fines are not returned back to the common pool. Masclet et al (2019) experimentally compared peerreporting (whistleblowing) treatments with and without positive externalities and found no difference in whistleblowing frequency when participants were informed that collected taxes were used to purchase carbon credits.…”
Section: Experimental Designmentioning
confidence: 99%